A new methodology for buckling, postbuckling and delamination growth behavior of composite laminates with delamination. (15th July 2021) - Shabanijafroudi, Nima; Ganesan, Rajamohan
Abstract: A methodology for predicting the buckling and postbuckling behavior of composite plates with delamination is proposed. The novelty of the new methodology lies in the built-in capability of addressing the fracture mechanics phenomena involved in the postbuckling regime. The formulation is derived based on a new laminate partitioning scheme which offers better displacement consistency in the vicinity of the crack tip and provides access to interlaminar tractions. The sublaminates created by the partitioning scheme are modeled using the first-order shear deformation theory. The continuity of the displacement field across the interfaces of the sublaminates is enforced using a penalty function method which is equivalent to considering high stiffness elastic bonds between the sublaminates. The equilibrium equations are derived using the stationary total potential energy principle and through the application of the Ritz method. The derived system of nonlinear equations is solved using an arc-length method. Irwin's crack closure integrals are employed for calculating the distribution of energy release rates corresponding to the three fracture modes individually. The validity of the fracture mechanics results is examined through the comparison of sample results with finite element results. The postbuckling results are verified through comparisons made with experimental data available in the literature.